CD57 identifies T cells with functional senescence before terminal differentiation and relative telomere shortening in patients with activated PI3 kinase delta syndrome. Issue 10 (14th June 2018) - Cura Daball, Paola; Ventura Ferreira, Monica Sofia; Ammann, Sandra; Klemann, Christian; Lorenz, Myriam R; Warthorst, Ursula; Leahy, Timothy Ronan; Conlon, Niall; Roche, Justin; Soler‐Palacín, Pere; Garcia‐Prat, Marina; Fuchs, Ilka; et al.
Abstract: Premature T‐cell immunosenescence with CD57 + CD8 + T‐cell accumulation has been linked to immunodeficiency and autoimmunity in primary immunodeficiencies including activated PI3 kinase delta syndrome (APDS). To address whether CD57 marks the typical senescent T‐cell population seen in adult individuals or identifies a distinct population in APDS, we compared CD57 + CD8 + T cells from mostly pediatric APDS patients to those of healthy adults with similarly prominent senescent T cells. CD57 + CD8 + T cells from APDS patients were less differentiated with more CD27 + CD28 + effector memory T cells showing increased PD1 and Eomesodermin expression. In addition, transition of naïve to CD57 + CD8 + T cells was not associated with the characteristic telomere shortening. Nevertheless, they showed the increased interferon‐gamma secretion, enhanced degranulation and reduced in vitro proliferation typical of senescent CD57 + CD8 + T cells. Thus, hyperactive PI3 kinase signaling favors premature accumulation of a CD57 + CD8 + T‐cell population, which shows most functional features of typical senescent T cells, but is different in terms of differentiation and relative telomere shortening. Initial observations indicate that this specific differentiation state may offer the opportunity to revert premature T‐cell immunosenescence and its potential contribution to inflammation and immunodeficiency in APDS. Abstract : Our results show that, in APDS patients, CD57 marks a functional senescence program not strictly related to the typical phenotypic pattern and transcriptional profile of that observed in healthy adult individuals. In APDS patients, CD57 expression and functional senescence may not be associated with relative telomere shortening.